2016
DOI: 10.1111/maec.12313
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral communities of the Eastern Lau Spreading Center and Valu Fa Ridge: community composition, temporal change and comparison to near‐vent communities

Abstract: Western Pacific hydrothermal vents will soon be subjected to deep-sea mining and peripheral sites are considered the most practical targets. The limited information on community dynamics and temporal change in these communities makes it difficult to anticipate the impact of mining activities and recovery trajectories. We studied community composition of peripheral communities along a cline in hydrothermal chemistry on the Eastern Lau Spreading Center and Valu Fa Ridge (ELSC-VFR) and also studied patterns of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 86 publications
2
18
0
Order By: Relevance
“…The diversity of the Mara4 assemblage could be the result of mixing vent endemic, non-symbiont reliant or not solely reliant species, such as A. rodriguezensis or B. septemdierum, in lower abundances, with filter feeding, carnivorous and scavenging taxa to form this peripheral community (Fabri et al, 2011;Sen et al, 2016;Goffredi et al, 2017). It has been suggested that anemones can tolerate low levels of hydrothermal fluids and temperatures, which has been measured for M. rimicarivora with a maximum tolerance of 25 • C at Ashadze vent field on the MAR (Fabri et al, 2011).…”
Section: Mara4 Assemblagementioning
confidence: 99%
See 2 more Smart Citations
“…The diversity of the Mara4 assemblage could be the result of mixing vent endemic, non-symbiont reliant or not solely reliant species, such as A. rodriguezensis or B. septemdierum, in lower abundances, with filter feeding, carnivorous and scavenging taxa to form this peripheral community (Fabri et al, 2011;Sen et al, 2016;Goffredi et al, 2017). It has been suggested that anemones can tolerate low levels of hydrothermal fluids and temperatures, which has been measured for M. rimicarivora with a maximum tolerance of 25 • C at Ashadze vent field on the MAR (Fabri et al, 2011).…”
Section: Mara4 Assemblagementioning
confidence: 99%
“…In general, the faunal zonation can be divided in an active vent fauna consisting of symbiotic taxa occurring close to fluid exits, often dominated by a single taxon in a distance related gradient according to their temperature tolerance and ability to persist in toxic fluid effluents (Sarrazin et al, 1997;Podowski et al, 2009;Sen et al, 2014), and mainly endemic secondary consumer vent taxa at greater distances to fluid effluents. The increasing distance to the active vent field results in a mix of vent taxa and background taxa in high abundances (Podowski et al, 2010;Marsh et al, 2012;Sen et al, 2016). This distance related taxonomic gradient has been studied in detail at the East Pacific Rise for hydrothermal vent communities, specifically after disturbance events (Tunnicliffe et al, 1997), for several gastropod species (Bates et al, 2005) and zooplankton distribution (Skebo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Austinograea williamsi was originally collected in abundance on three active vent fields along the crest of the spreading center, at about latitude 18°N and longitude 144°E, 3600 m depth; later found on vent sites of the Mariana Trough at 13°23.7'N, 143°55.2'E, about 1450 m depth, andat 18°12.9'N, 144°42.5'E, about 3600 m depth (Hessler et al 1988;Hessler & Martin 1989;Guinot 1990;Hessler & Lonsdale 1991;Tsuchida & Fujikura 2000;Tsuchida & Hashimoto 2002;Martin & Haney 2005;Segonzac 2006;McLay 2007;Ng et al 2008;Zelnio & Hourdez 2009;Hamasaki et al 2010: fig. 1;Podowski et al 2010;Sen et al 2013Sen et al , 2014Sen et al , 2016Kojima & Watanabe 2015). Records of A. williamsi from the Lau and North Fiji Back-Arc Basins appear to be quite doubtful and at the very least need to be checked.…”
Section: Introductionmentioning
confidence: 99%
“…; Hashimoto et al 1989, as bythograeid sp. ;Guinot 1990in Desbruyères & Segonzac 1997Galkin 1997;Tsuchida & Hashimoto 2002;Komai & Segonzac 2004;Martin & Haney 2005;López-González et al 2005;Segonzac 2006;Guinot & Segonzac 2006a, b;Desbruyères et al 2006b;McLay 2007;Shields & Segonzac 2007;Ng et al 2008;Erickson et al 2009;Corbera & Segonzac 2010;Podowski et al 2010;Mateos et al 2012;Kim et al 2013Kim et al , 2014Sen et al 2013Sen et al , 2014Sen et al , 2016Yang et al 2013;Hui et al 2017). Some of these records, however, deserve to be checked.…”
Section: Introductionmentioning
confidence: 99%